How the International Criminal Court exercises its jurisdiction - CHERIET, Souheila (Journal of Human Sciences, 2025)
It was stated in the statute of the International Tribunal that the latter established its revolutionary mandate only on the most dangerous part that worries the international community, to the extent that it completes it without detracting from or activating national exhaustion, and that the drafters of this statute would have completed setting complex conditions for it to complete the executive work. According to its international jurisdiction, it must be aware of the occurrence of this international quantity, and the Rome Statute specifies how to bring the matter to the court, and also specifies the persons legally qualified to bring it before it, and the role of states in presenting and receiving the perpetrators of the international contribution, and also specifies the procedures necessary for effective filing, and between This study is the jurisdiction of the judicial court, which fully determines the basis of the type of crime and the person who prosecuted it, and also whether the court is competent in complementing it with the jurisdiction of the national judicial court, and introduces us to the judicial instructions, and then explains to us the ways to appeal the judge who issued it.